MECHANISMS IN ENDOCRINOLOGY: Tissue-specific activation of cortisol in Cushing's syndrome. Issue 2 (August 2016) - Morgan, Stuart A; Hassan-Smith, Zaki K; Lavery, Gareth G
Abstract : Glucocorticoids are widely prescribed for their anti-inflammatory properties, but have 'Cushingoid' side effects including visceral obesity, muscle myopathy, hypertension, insulin resistance, type 2 diabetes mellitus, osteoporosis, and hepatic steatosis. These features are replicated in patients with much rarer endogenous glucocorticoid (GC) excess (Cushing's syndrome), which has devastating consequences if left untreated. Current medical therapeutic options that reverse the tissue-specific consequences of hypercortisolism are limited. In this article, we review the current evidence that local GC metabolism via the enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) plays a central role in mediating the adverse metabolic complications associated with circulatory GC excess – challenging our current view that simple delivery of active GCs from the circulation represents the most important mode of GC action. Furthermore, we explore the potential for targeting this enzyme as a novel therapeutic strategy for the treatment of both endogenous and exogenous Cushing's syndrome.